Nucleophilic Substitution on Polyfluorinated Pyridine and Pyrimidine Rings for Construction of Lanthanide Ligands - Starck, Matthieu; Charbonnière, Loïc; Ziessel, Raymond (Synthesis, 2013)
The use of nucleophilic substitution of fluoride attached to azaaromatics has been used to provide polypyrazolyl-substituted pyridine and pyrimidine ligands of potential value as lanthanide ion complexants. Ester substituents on the pyrazolyl groups can be reduced to the corresponding alcohol, which can in turn be converted to the bromide, then reacted with diethyl iminodiacetate to provide highly functionalized derivatives. Base hydrolysis converts these to polyanionic ligands, although the overall process is only efficient in the case of a pyridine core. The pyridine ligand with three pyrazolate and thus six carboxylate substituents forms stable, water-soluble Eu(III) and Tb(III) complexes displaying interesting spectroscopic properties with excited state lifetimes of about 1.6 ms and 1.0 ms, respectively, and quantum yields in the 4.5% to 13% range in water. Uncoordinated carboxylate groups in these complexes can be used for their grafting to polyacrylate polymer beads.
Keywords: pyrazolate; pyridine; bipyrimidine; polycarboxylate; lanthanides; labeling; acrylic beads